2020
DOI: 10.1039/c9cp06523g
|View full text |Cite
|
Sign up to set email alerts
|

Do defects in PAHs promote catalytic activity in space? Stone–Wales pyrene as a test case

Abstract: Using density functional theory (DFT), we studied the formation of H2 on Stone–Wales pyrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The first hydrogen atom to bond with the graphene sheet must overcome a calculated activation barrier of around 0.16 eV to chemisorb, , close to the experimentally determined value of 0.2 eV . This barrier can be overcome by rapid, quasi-elastic energy loss by the impinging hydrogen atom. , The Stone–Wales defect was found to lower the barrier toward the initial C–H bond formation in a pyrene model system . No activation barrier is found for a second hydrogen atom forming a C–H dimer at the para carbon positions, , though bonding competes with H 2 recombination and abstraction at the ortho position.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The first hydrogen atom to bond with the graphene sheet must overcome a calculated activation barrier of around 0.16 eV to chemisorb, , close to the experimentally determined value of 0.2 eV . This barrier can be overcome by rapid, quasi-elastic energy loss by the impinging hydrogen atom. , The Stone–Wales defect was found to lower the barrier toward the initial C–H bond formation in a pyrene model system . No activation barrier is found for a second hydrogen atom forming a C–H dimer at the para carbon positions, , though bonding competes with H 2 recombination and abstraction at the ortho position.…”
Section: Introductionsupporting
confidence: 63%
“…27,28 The Stone−Wales defect was found to lower the barrier toward the initial C−H bond formation in a pyrene model system. 29 activation barrier is found for a second hydrogen atom forming a C−H dimer at the para carbon positions, 27,30−32 though bonding competes with H 2 recombination and abstraction at the ortho position. It is possible that instead of chemisorbing, a second hydrogen atom could physisorb and remain mobile on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical methods can play an important role in identifying chemical routes and reaction products. 5 , 6 , 86 , 87 However, due to the large computational cost, little has been done to study the chemical and physical properties of PAHs on minerals. 53 , 54 In this work, we identified a DFT method that can accurately compute the binding energy of aromatic molecules on a mineral surface.…”
Section: Discussionmentioning
confidence: 99%
“…They have been identified through their vibrational signature in infrared spectra and thought to be involved in many important processes that regulate the physical conditions of star-forming regions . Specifically, PAHs have been extensively studied as catalysts for interstellar H 2 formation. They may also play a role as reagents in many reactions involving atoms, ions, and molecules that contribute to the rich organic inventory of space . Finally, it has been suggested that PAHs may be more directly involved in the origin of life by providing a convenient assemblage structure for RNA …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation